Metabolomics in Heart Failure Patients: Hype and Hope - Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2016)
Heart failure remains a leading cause of death in patients with established cardiovascular disease. The biomarkers reflecting staging and evolution of HF appear to be promised tool to risk stratification and target-based therapy. In the editorial adaptive metabolic transitions of HF with reduced and preserved left ventricular ejection fraction are considered. It has discussed the role of metabolites in the regulating function of the failing heart. The use of metabolites, i.e. polyamines, putrescine, spermidine, spermine, ornithine decarboxylase, and acylcarnitine, in patients with HF is considered. Future directions regarding molecular biology techniques, which substantially contribute to assay of metabolic profile in HF patients aimed improving clinical outcomes, response to the individualized therapy, are emphasized.
Keywords: Heart failure; Metabolism; Biomarkers; Clinical outcomes; Metabolomics; Proteomics